Effect of steam explosion on nutritional composition and antioxidative activities of okra seed and its application in gluten‐free cookies. Issue 8 (30th June 2020) - Hu, Lei; Guo, Jiamin; Zhu, Xiwei; Liu, Rui; Wu, Tao; Sui, Wenjie; Zhang, Min
Abstract: Health‐conscious consumers are increasingly interested in gluten‐free (GF) foods. Raw okra seed (ROS) flour and steam‐exploded okra seed (SEOS) flour were explored for developing GF cookies with high nutritional values and in vitro enzymatic digestion. Results indicated that the steam explosion exhibited significant effects on enhancing the release of dietary fibers and lipids in okra seed flour at moderate explosion pressure. Although steam explosion caused the loss of flavonoid compounds, moderate high explosion pressure enhanced the release of total phenolics ranged from 294.57 to 619.07 mg GAE/100 g DM with significantly improved DPPH radical scavenging activity (from 18.78% to 67.34%) and ferric reducing antioxidant power (from 13.37% to 149.04%). The rapidly digestible starch (RDS) content in GF cookies decreased with increasing steam explosion severity, whereas slowly digestible starch (SDS) and resistant starch (RS) contents significantly increased from 36.91% to 40.92% and from 2.50% to 9.06%, respectively. Steam explosion is an effective technique for enhancing the release of nutrients like dietary fiber and total phenolics, and okra seed flour, especially SEOS flour, can be alternative choices to provide food functional materials for developing various GF food products. Abstract : Raw okra seed flour and steam‐exploded okra seed (SEOS) flour were explored for developing gluten‐free (GF) cookies with high nutritional values and in vitro enzymatic digestion. Steam explosion is an effective technique for enhancing the release of nutrients like dietary fiber and total phenolics, and okra seed flour, especially SEOS flour, can be alternative choices to provide food functional materials for developing various GF food products.